Development and usability testing of the e‐EXCELS tool to guide cancer survivorship follow‐up care. Issue 1 (18th October 2019) - O'Malley, Denalee M.; Davis, Stacy N.; Devine, Katie A.; Sullivan, Brittany; Bator, Alicja; Clemow, Lynn; Ferrante, Jeanne M.; Findley, Patricia A.; Miller, Suzanne M.; Hudson, Shawna V.
Abstract: Objective: The aim of this study is to describe a user‐centered (e.g., cancer survivors and clinicians) development process of an eHealth tool designed to facilitate self‐management of cancer survivorship follow‐up care. Methods: Guided by Cognitive‐Social Health Information Processing (C‐SHIP) model and informed by core self‐management skills, we engaged in a user‐centered design process. In phase I, we conducted in‐depth interviews with survivors of breast (n = 33), prostate (n = 4), and colorectal (n = 6) cancers, and (n = 9) primary care providers to develop content and design of the web tool. Phase II utilized iterative user testing interviews (n = 9) to test the web‐based tool prototype. Data from both phases were independently coded using a template/content analytic approach. Results: The top 5 functions identified in phase I for the web‐based platform included: (a) educational materials to learn and prepare for health encounters (80%); (b) questions for health providers (74%); (c) ability to track contact information of providers (67%); (d) provide general information (64%); and, (e) support information (62%). Users of the prototype reported patient burden, tool fatigue, introduction timing of the tool, relevance, and security/privacy as concerns in phase II. Conclusions: This study demonstrates the value of using a theoretically informed and user‐centered design process to develop relevant and patient‐centered eHealth resources to support cancer survivorship. A larger study is needed to establish the efficacy of this eHealth tool as an intervention to improve adherence to follow‐up care guidelines.